INTERNATIONAL TRADE PAYMENT AND EXCHANGE RATE: THE TRADE BALANCE BETWEEN THE US AND OTHER COUNTRIES CAN IMPACT THE STRENGTH OF THE DOLLAR - Ortiqov , Maxammadjon Adxamjon o‘g‘li (Educational Research in Universal Sciences, 2023)
In this an explanation of the research aimed at identifying and optimizing the study methodology of the dynamics of the trade balance between the US and other countries can impact the strength of the dollar. This research analaysis an increase in exports can lead to a stronger dollar,while an increase in imports can lead to a weaker dollar. The research shows in the world, 40% of global trade is invoiced in US dollar (USD), despite the fact that United State accounts for only 10% of global imports and exports depending on the general economic conditions. Also, proposals and recommendations given on the method of regulating and organizing the formation of foreign exchange reserves in the Special Drawing Rights, as well as the influence of international trade between countries on the dynamics of the exchange rate In addition to that the dollar has also a unique role in the international payment system as main reserve and funding currency. Due to its extensive use in international trade and finance, fluctuations in the value of the dollar operate noticible foreign spillovers, much stronger than those implied by an appreciation of the euro (the second most widely used currency in global invoicing) or the yen. All in all, the USD is a pivotal currency in international trade and finance system, and its influence is likely to continue.